(untitled) (Clinics, 2023)
In Malignant Hilar Biliary Stricture (MHBS) palliative biliary drainage is a frequent strategy, improving the quality of life, reducing pruritus, loss of appetite and relieving cholangitis. The endoscopic approach is an effective, although challenging procedure. This study aimed to evaluate technical and clinical success rates of biliary drainage by ERCP. This is a retrospective study including all patients with MHBS referred to Instituto do Cancer do Hospital de São Paulo (ICESP) submitted to biliary drainage by ERCP, between January 2010 and December 2017. Multivariable logistic regression was performed to evaluate predictors of clinical failure, as total bilirubin levels, Bismuth classification, number of hepatic sectors drained and presence of cholangitis. In total, 82 patients presenting unresectable MHBS were included in this study. 58.5% female and 41.5% male, with a mean age of 60±13 years. Bismuth classification grades II, IIIA, IIIB and IV were noted in 23.2%, 15.9%, 14.6% and 46.3%, respectively. Technical and clinical success was achieved in 92.7% and 53.7% respectively. At multivariable logistic-regression analyses, Bismuth IV strictures were related to higher clinical failure rates when compared to other strictures levels, with an Odds Ratio of 5.8 (95% CI 1.28‒20.88). In conclusion, endoscopic biliary drainage for malignant hilar biliary stricture had a high technical success but suboptimal clinical success rate. Proximal strictures (Bismuth IV) were associated with poor drainage outcomes.